Mariculture pond water body biological nutrient and preparation method thereof - LU XI; ZHANG QIHUA; ZHU XUEZHI; LIU XUANHUA; MA XUEKUN; WANG HAO; CHENG KAIMIN; YAO CHUNFENG; LI SUYING; ZHANG HAN; ZHENG SHIXUAN; LIU LIYAN; et al. (2016)
The invention discloses a mariculture pond water body biological nutrient and a preparation method thereof. The nutrient comprises the following components in parts by weight: 40 parts of 50% phosphoric acid, 30-50 parts of tap water, 20 parts of shrimp shell powder, 10 parts of peanut bran powder, 10 parts of squid organ meal, 0.1 part of ferrous sulfate, 0.3 part of copper sulfate, 0.6 part of zinc sulfate, 0.3 part of manganese sulfate, 6 parts of fresh beer yeast paste and 0.05-0.08 part of papain. The biological nutrient is used in mariculture pond water bodies so as to promote the growth of alga and zooplanktons, perfect food chains in the culture water bodies are constructed easily and the culture water quality can be effectively controlled, the nutrient can be used as an aquatic animal feed additive and is added in a low-temperature granulation process, and can be used as a feed protein type raw material or an aquatic animal attractant; after adding the nutrient, the prepared feeds are used in the aqu